A High Prevalence of Carotid Artery Stenosis in Male Patients Older Than 65 Years, Irrespective of Presenting Clinical Manifestation of Atherosclerotic Diseases. (May 2013) - Kazemi-Bajestani, Seyyed Mohammad Reza; van der Vlugt, Maureen; de Leeuw, Frank-Erik; Blankensteijn, Jan D.; Bredie, Sebastian J. H.
This study investigated the prevalence of carotid artery stenosis (CS) and the association with various risk factors in male patients (>65 years) diagnosed with cardiovascular diseases. Duplex sonography of the carotid arteries was performed in 434 of 473 eligible patients of whom 118 (27.8%) patients had significant CS ≥50%. The prevalence and severity of CS did not differ between patients who presented with neurological symptoms or acute coronary syndrome/peripheral artery disease (30.8% vs 25.9%, respectively). Among patients with CS, a higher rate of current smoking, a higher systolic blood pressure, and a lower glomerular filtration rate were observed compared with patients without CS. A history of coronary artery bypass graft was a significant predictor of the presence of CS ( P = .003, odds ratio [OR] = 2.70 [1.40-5.19]). The prevalence of CS in elderly males with manifest atherosclerotic disease is high, irrespective of presenting clinical manifestation.